Healthcare systems, the State, and innovation in the pharmaceutical industry - Ignacio José Godinho Delgado
Abstract: This article discusses the relations between healthcare systems and the pharmaceutical industry, focusing on state support for pharmaceutical innovation. The study highlights the experiences of the United States, United Kingdom, and Germany, developed countries and paradigms of modern health systems (liberal, universal, and corporatist), in addition to Japan, a case of successful catching up. The study also emphasizes the experiences of China, India, and Brazil, large developing countries that have tried different catching up strategies, with diverse histories and profiles in their healthcare systems and pharmaceutical industries. Finally, with a focus on state forms of support for health research, the article addresses the mechanisms for linkage between health systems and the pharmaceutical industry, evaluating the possibilities of Brazil strengthening a virtuous interaction, favoring the expansion and consolidation of the Brazilian health system - universal but segmented ‒ and the affirmation of the innovative national pharmaceutical industry.